2015
DOI: 10.1299/jamdsm.2015jamdsm0036
|View full text |Cite
|
Sign up to set email alerts
|

Optimum position and orientation of handrail for sit-to-stand movement

Abstract: The sit-to-stand (STS) movement is performed throughout the day, and providing handrails is one method of making the STS movement easy. However, designers may have determined the installation position of handrails using intuition and trial and error. The aim of this study is to determine the optimum position and orientation of handrails by minimizing the quantified physical load of the STS movement. Twelve university students participated, and eight electromyograms (EMGs), namely, of the brachioradialis, flexo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the maximum knee moment was smaller when the handrail was on the impaired side than it was on the healthy side. Chihara et al [ 12 ] determined the optimum position and orientation of handrail for STS movement, finding that when the handrail was tilted back 38.4° and the height was 1.3 times the height of the acromion, the total physical load (formulated as the weighted sum of the EMGs) was the lowest. Kato et al [ 13 ] designed a new curved-angled handrail and found that the reaction forces generated in the anterior posterior and upward downward directions during STS movements using the curved-angled handrail were significantly higher than those generated using a conventional vertical handrail (VH; P < .001).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the maximum knee moment was smaller when the handrail was on the impaired side than it was on the healthy side. Chihara et al [ 12 ] determined the optimum position and orientation of handrail for STS movement, finding that when the handrail was tilted back 38.4° and the height was 1.3 times the height of the acromion, the total physical load (formulated as the weighted sum of the EMGs) was the lowest. Kato et al [ 13 ] designed a new curved-angled handrail and found that the reaction forces generated in the anterior posterior and upward downward directions during STS movements using the curved-angled handrail were significantly higher than those generated using a conventional vertical handrail (VH; P < .001).…”
Section: Introductionmentioning
confidence: 99%